SEISMIC ATTENUATION TOMOGRAPHY STUDY WITH THE SPECTRAL FITTING METHOD USING VOLCANIC EARTHQUAKE DATA OF MOUNT GUNTUR 2001-2004 - PRATAMA (NIM 12403005), RIZKI
Earthquake data can be used to image the earth's interior structure, one of the methods is seismic tomography. In this study, the internal structure of Mount Guntur has been imaged using the seismic attenuation tomography, with the research area covering a volume of 20x20x20 km3 and a block size of 2x2x2 km3 used in the 3D model parameterization. The locations of hypocenters were determined by using a three-circle method followed by a grid search in the cross section area using the arrival time data of P- and S-waves data. In the determination of the P- and S-wave attenuation, we employ the spectral fitting method by using the P- and S-wave amplitudes independently. The result of data processing shows that the hypocenter positions are in the depth around 10 km from the top of Mount Guntur. The resulting velocity tomograms in the depth around 10 km depict a negative velocity anomaly and the seismic attenuation tomograms show a high attenuation anomaly in the depth around 4 km from the top of Mount Guntur. This high seismic attenuation zone can be interpreted as a high temperature area beneath Mount Guntur, which may be related to the location of magma chamber.